2017
DOI: 10.1073/pnas.1612385114
|View full text |Cite
|
Sign up to set email alerts
|

Properdin binding to complement activating surfaces depends on initial C3b deposition

Abstract: Two functions have been assigned to properdin; stabilization of the alternative convertase, C3bBb, is well accepted, whereas the role of properdin as pattern recognition molecule is controversial. The presence of nonphysiological aggregates in purified properdin preparations and experimental models that do not allow discrimination between the initial binding of properdin and binding secondary to C3b deposition is a critical factor contributing to this controversy. In previous work, by inhibiting C3, we showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 51 publications
2
64
0
Order By: Relevance
“…Values in parentheses are for highest resolution shell. The EMBO Journal The structure and function of properdin Dennis V Pedersen et al been raised concerning whether FP actually performs C3b-independent pattern recognition (Harboe et al, 2012(Harboe et al, , 2017. Potentially FPc enables detailed structural analysis of FP and its complexes with small molecule ligands mimicking patterns recruiting FP independent of prior C3b deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Values in parentheses are for highest resolution shell. The EMBO Journal The structure and function of properdin Dennis V Pedersen et al been raised concerning whether FP actually performs C3b-independent pattern recognition (Harboe et al, 2012(Harboe et al, , 2017. Potentially FPc enables detailed structural analysis of FP and its complexes with small molecule ligands mimicking patterns recruiting FP independent of prior C3b deposition.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,13,15,29 Conversely, in other cases properdin has been shown to act only as a positive regulator, requiring preceding C3b deposition to bind. 30,31 To better understand the mechanism of properdin binding and function in vivo, we explored an experimental model of anti-GBM disease in WT, properdin KO, and C3 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…These results should be interpreted carefully, given that the experiments were all done in a serum environment in the presence of intact C3. Others have shown that, in serum, properdin binding to multiple targets is fully dependent on C3 [32].…”
Section: Recognitionmentioning
confidence: 99%